ROLE OF CONSUMER ETHNOCENTRISM ON GENERATION Z PURCHASE INTENTION TOWARD CHINESE HOME APPLIANCES PRODUCTS IN JABODETABEK - Jacelyn Zerlina Loraine; Benny Aristo (Faculty of Economics and Business Universitas Pelita Harapan, 2025)
Chinese home appliances continue to dominate the market, with imports seeing significant growth. This paradox highlights the tension between national pride and the appeal of foreign products. This research seeks to assess the impact of Indonesian consumer ethnocentrism, general country image of China, and product country image of China on Generation Z purchasing intentions for home appliances products from China. This research used survey method and data collection was conducted using a questionnaire distributed to 208 respondents who are familiar with Chinese home appliances products. The sampling technique used was purposive sampling, and data analysis was conducted with the SmartPLS version 4 software. The research results shows that Indonesian consumer ethnocentrism has an influence on general country image of China, Indonesian consumer ethnocentrism has an influence on product country image of China, Indonesian consumer ethnocentrism has an influence on purchase intention of Chinese home appliances, general country image of China has an influence on product country image of China, general country image of China has an influence on purchase intention of Chinese home appliances and product country image of China has an influence on purchase intention of Chinese home appliances. The findings of this research are hoped to serve as a strategy for both local and global companies in addressing consumer preferences in the Indonesian home appliances market. The Managerial implication of this research is recommending domestic companies to prioritize cultural values and Multinational companies can localize products and support local communities to increase familiarity and gain local consumer support.